The Dialectical Relationship of the Arbitrariness and Iconicity of Linguistic Semiotics - Lyu, Lirong (Pacific International Journal, 2024)
The enduring debate surrounding the arbitrariness and iconicity of linguistic signs centers on the relationship between form and meaning, or signifier and signified. This study aims to clarify the dialectical relationship between these two foundational principles in linguistics. Historically, arbitrariness, as proposed by Ferdinand de Saussure, posits that the connection between a linguistic sign’s form and its meaning is conventional and lacks inherent justification. Conversely, iconicity suggests a natural or motivated connection between form and meaning, a view supported by cognitive and functional linguistics. This paper critically reviews the historical and contemporary arguments from both camps, highlighting significant contributions from scholars such as Saussure, Peirce, and Haiman. Through a comprehensive analysis, it is demonstrated that arbitrariness and iconicity are not mutually exclusive but coexist at different levels within language systems. The paper argues for a nuanced understanding that considers both synchronic and diachronic perspectives, ultimately suggesting that these two principles can complement each other, providing a deeper insight into the nature and function of linguistic signs. This study contributes to the broader discussion on the inherent characteristics of language, with implications for linguistic theory, language teaching, translation, and cognitive science.